(untitled) (Journal of Partial Differential Equations, 2014)
" The fractional derivatives in the sense of Caputo, and the homotopy perturbation method are used to construct the approximate solutions for nonlinear variant Boussinesq equations with respect to time fractional derivative. This method is efficient and powerful in solving wide classes of nonlinear evolution fractional order equations."